Clinical teaching behaviors and its effectiveness to learning: IIUM. A comparison between faculty and undergraduate nursing students’ perception in Malaysia - Nik Mohamad, Fathullah; Mohamed Ludin, Salizar (2014)
Background: Clinical experience is important in nursing learning process, it provide learners with knowledge, skills and attitudes they need in the future. Clinical faculty is a critical determinant for quality clinical learning experiences of student nurses. It is believed that a better understanding of the perceptions of clinical teaching behaviors between student nurses and educators will enhance clinical teaching. Significant of study: The finding will be the basis for recommendations in teaching students in the clinical settings, which will help in the development of current faculty and to improve the quality of clinical education Problem Statement: Despite researches conducted on perceptions of faculty and students on the effective characteristics of faculty in classroom setting, researches regarding faculty characteristics that are effective and its influences to learning in the clinical setting are very limited and none published in Malaysia. Aim: This study aim to explore faculty’s clinical teaching behaviors and its influence to students’ learning, from the Malaysian undergraduate nursing students’ perspectives Methods: A cross-sectional, co-relational study design was used. University Ethical Committee approval obtained. Modified NCTEI (Kube 2010) was used for data collection and data were subject to descriptive and inferential analysis Result: Overall, Year 3 & 4 students shows positive perception. Most clinical teaching behaviors influence learning, with strong positive association. The association between clinical behaviors and influence of learning were significant. Faculty being competence was the most, while faculty personality was the least influence to student learning Conclusion: Participants were able to identify the good behaviors and basically the faculties are doing well. Novice can use the positive association. finding as a guide in clinical practice.